Clostridium difficile infection in the Lao People's Democratic Republic: first isolation and review of the literature. - Cheong, E; Roberts, T; Rattanavong, S; Riley, T; Newton, P; Dance, D (BioMed Central, 2017)
Background Current knowledge of the epidemiology of Clostridium difficile infection in Asia, and in particular the Greater Mekong Subregion, is very limited. Only a few studies from Thailand and Vietnam have been reported from the region with variable testing methods and results, and no studies from Lao People’s Democratic Republic (PDR). Therefore we investigated the presence of C. difficile in a single centre in the Lao PDR and determined the ribotypes present. Method Seventy unformed stool samples from hospital inpatients at Mahosot Hospital, Vientiane, were tested for the presence of C. difficile using selective differential agar and confirmed by latex agglutination. C. difficile isolates were further characterised by ribotyping and toxin gene detection. Results C. difficile was isolated from five of the 70 patients, and five different ribotypes were identified (014, 017, 020, QX 107 and QX 574). Conclusion This is the first isolation of C. difficile from human stool samples in the Lao PDR. These results will add to the limited amount of data on C. difficile in the region. In addition, we hope this information will alert clinicians to the presence of C. difficile in the country and will help inform future investigations into the epidemiology and diagnosis of C. difficile in Lao PDR.